3(x-2)=2x+6(x-1)

Simple and best practice solution for 3(x-2)=2x+6(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)=2x+6(x-1) equation:



3(x-2)=2x+6(x-1)
We move all terms to the left:
3(x-2)-(2x+6(x-1))=0
We multiply parentheses
3x-(2x+6(x-1))-6=0
We calculate terms in parentheses: -(2x+6(x-1)), so:
2x+6(x-1)
We multiply parentheses
2x+6x-6
We add all the numbers together, and all the variables
8x-6
Back to the equation:
-(8x-6)
We get rid of parentheses
3x-8x+6-6=0
We add all the numbers together, and all the variables
-5x=0
x=0/-5
x=0

See similar equations:

| 2=3n-1+1 | | 5x=7x/12 | | 3x=-3(x+2) | | j-5=2 | | 16=2x-x/4 | | 21x-9+53=180 | | 15m-22=-10m+28 | | Q=25-0.2p | | 3x+5=25+13x | | 17x+26=6x+x+56 | | x+23/28=2 | | x-30+2x+135=180 | | -2(2x)=-4 | | 10+3k=23 | | 15y-14=8y+35 | | 7n^2-2=-102 | | 13=1+9x | | -2(18-3x)=7x2x | | W-3/3-1=w+1/2 | | 3(x-7)-8x=9 | | 6m+4(2m+6)=10 | | 5+6n=11+3n | | 0.4^2+1^2=e^2 | | x+2x-10=17 | | -5m+4=-3m+12 | | -3/5x+5=-13 | | 4c-4=-7/2 | | ((-20x^2)+(-50x)+42=0 | | 6x+1=3(2x+5) | | 4f+15=-72 | | -3n+3(4n+15)=21 | | 1÷2(6g+2)=12 |

Equations solver categories